Determinasi Kepuasan Pelayanan Front Office Pasca Penggabungan Kantor BSI KCP Ponorogo - Ika Fitriah; Husna Ni'matul Ulya (Institut Agama Islam Negeri Ponorogo, 2024)
Introduction: This research aims to better understand the factors influencing front-office service satisfaction after the office merger at BSI Ponorogo Soetta. The emergence of queuing problems felt by customers and front office officers not being ready to provide service causes customer satisfaction to decrease. This type of research is quantitative research with a sample size of 100 respondents using non-probability sampling techniques in the form of purposive sampling. The data obtained was then analyzed using the SPSS statistical program. This analysis consists of validity tests, reliability tests, classical assumption tests (normality test, multicollinearity test, heteroscedasticity test), and multiple regression tests (partial test, simultaneous test, and determination test). The results of the research are that partially and simultaneously, the variables tangible, reliability, responsiveness, assurance, and empathy influence customer satisfaction in the front office after the merger of the BSI KCP Ponorogo office with an R2 value of 0.911, meaning that it can explain variations in service quality of 91.1% and variables influence the remaining 8.9%.